Biological Characteristics of Cloned Populations of Herpes Simplex Virus Types 1 and 2 - Smith, Jerry W. (1971)
By using cloned types 1 and 2 herpes simplex virus, obtained by selecting large and small plaques produced by material from human lesions, studies were performed to compare properties between preparations of each type. Regarding the rate of inactivation by ultraviolet light, no differences were found between the two antigenic types and none between the preparations obtained from either type. In contrast, type 1 preparations were found to be more readily inactivated at 45 C than type 2. Plaque size of cloned preparations changed by passage in cell culture. A broader range of plaque sizes was obtained, and average plaque size was larger. After 20 passages, preparations obtained from different types gave rise to one of three kinds of cytopathic effect. The cytopathic effect produced by type 1 preparations remained as before 20 passages and consisted of round cells in a compact central mass. For type 2, two kinds of cytopathic effect were seen in cloned preparations. This consisted of aggregates of round cells (seen in preparations before 20 passages) or of large, loose aggregates of round cells of various sizes. Results from neutralization studies using virus before and after 20 passages in cell culture versus antisera prepared against live or ultraviolet-inactivated virus showed no differences between cloned preparations obtained from a given type.